The Influence of the PjBL Learning Model on Improving Motivation and Learning Outcomes of Fifth Grade Elementary School Students - Handayani, Tri Emy; Nissa, Ana Fitrotun; Masjid, Akbar Al (Universitas Pendidikan Ganesha, 2025)
Education is a crucial tool for developing high-quality, competitive human resources in the global era. In the The learning process in the classroom still tends to be conventional. Teachers are more dominant in using lecture methods and giving assignments. This causes students to be passive, less involved in the learning process, and has an impact on low motivation and learning outcomes. This study aims to analyze the application of the Project-Based Learning (PjBL) model on the learning motivation and science learning outcomes of fifth-grade elementary school students on the topic of ecosystems. This study uses a quantitative approach with a quasi-experimental design, namely the Nonequivalent Control Group Design. This study involved two elementary schools with 15 students, designated as the experimental group, who received learning through the Project-Based Learning (PjBL) model. Another elementary school with 14 students became the control group, which received conventional learning methods. Data collection was carried out through pretests and posttests for learning outcomes, as well as motivation questionnaires administered before and after the learning session. The collected data were analyzed statistically through several stages: normality and homogeneity tests, independent sample t-tests, and N-Gain tests. The main results of this study indicate that the Project-Based Learning (PjBL) model is more effective in improving fifth-grade students' science learning outcomes on the topic of ecosystems compared to conventional teaching methods. The implications of this research emphasize the importance of implementing an innovative, student-centered learning model, so that teachers no longer act as the sole source of information, but rather as facilitators who guide students in exploring and discovering knowledge through real experiences.